SPECTRAL CHARACTERISTIC COLOUR (RED , GREEN , BLUE) OF Acacia mangium IN SITE 23B, RPH MARIBAYA, BKPH PARUNG PANJANG, KPH BOGOR, WEST JAVA - Abdalla, Damario
Forest protection management are important activities and integrated from forest resource management system. One of the activities in forest protection is evaluating stand health in a particular forest region. These activities are important because it helps decision making to perform sustainable forest management. Evaluating stand health in a bigger scale needs more cost, time, and manpower. To overcome this obstacle, there is a need of supporting technology. The technology also needs to suffice within the development of remote sensing. flying drone is the suitable technology that could evaluate stand health. This research has the goal to determine spectral characteristic of A.mangium leaf in order to identify the area and position of sick trees. This reseach are excuted in A.mangium stand at KPH Bogor. The method that is being used are hyperspectral imaging analysis to determine the characteristic of RGB(Red,Green,Blue). Spectral analysis are sampled from 85 trees on 7 plot at site 23B RPH Maribaya BKPH Parung Panjang KPH Bogor using simple random sampling. The result of this research shows that trees in healthy condition, sick condition, and dead conditition has different spectral RGB value. RGB value for healthy trees are 121-149(B1),167-189(B2), 120-142(B3). For sick trees the RGB value are 151-165(B1), 183-205(B2), 145-165(B3). For dead trees the RGB values are 192-202(B1), 202-212(B2), 167-199(B3). As trees condition worsen, the RGB value increases. The pattern of RGB band composition are similar but has different value. This indicates the changing process of leaf colour from healthy to sick. On the other hand the interval of RGB band is small enough to notice there is a difference in colour of trees status. This research shows that spectral analysis from drone image could be used to analyse forest’s stand health